Acute, Subchronic, and Genetic Toxicity Assessments of a Composition of Citrus aurantifolia Fruit Rind and Theobroma cacao Seed Extracts - Sundararaju Dodda; Sujatha Polavarapu; Krishnaraju Venkata Alluri; Trimurtulu Golakoti; Krishanu Sengupta (Journal of Toxicology)
LN19183 is a standardized composition of Citrus aurantifolia (Christm) Swingle (CA) fruit rind and Theobroma cacao L. (TC) seed extracts that have recently been demonstrated to increase resting energy expenditure (REE) and reduce body fat in rats. CA and TC are important herbs in traditional medicine for various health benefits. The present study evaluates the comprehensive toxicity of LN19183 in acute, subchronic, and genetic toxicity studies following the guidelines of the Organization for Economic Co-operation and Development (OECD) for testing chemicals. The acute oral and dermal and 90-day subchronic oral toxicities were performed in rats, and acute dermal and eye irritations were performed in rabbits. In the subchronic toxicity study with a 28-day recovery period, male and female Sprague Dawley rats were orally gavaged with daily LN19183 doses of 500, 1000, or 2000 mg/kg body weight (BW). Furthermore, the genetic toxicity studies included mutagenicity in bacteria, chromosome aberration, and micronucleus assays in human blood mononuclear cells in vitro and micronucleus assay in Swiss albino mice bone marrow in vivo. Acute and subchronic repeat dose oral toxicity studies showed no adverse events, clinical signs, or mortality. All animals exhibited normal food and water intake and natural BW gain. In the 90-day study, LN19183 did not induce major changes in hematology, biochemical evaluations, and urine analysis; gross and histopathological findings did not show any treatment-related lesions or abnormality. The no observed adverse effect level (NOAEL) of LN19183 supplementation was 2000 mg/kg BW/day. In the genetic toxicity studies, LN19183 treatment did not show significant increases in the revertant bacterial colonies, chromosomal aberrations, or number of micronucleated cells. The present observations affirm that oral consumption of LN19183 is safe, and this botanical composition is nonmutagenic and nonclastogenic.